A grey wolf optimization based approach to provide ancillary services for battery owners - Çakır Muhammed Turhan; Esen Irem Sude; Ceylan Oğuzhan; Zehir Mustafa Alparslan; Zanaj Elma (Serbian Journal of Electrical Engineering, 2025)
As is known, batteries have started to be used increasingly in both power distribution and transmission networks. This study develops a near-optimal approach for ancillary services in power networks from the perspective of the battery owner. We first model the optimization algorithm for the battery owner, then utilize a grey wolf optimization approach, where near-optimal actions are selected daily from available services. We use real data of frequency, voltage magnitude, combined home and Photovoltaic system, and transformer load to perform the simulations. The simulation results show that battery owners may profit from these services and help the system operators solve the issues such as over-voltage, under-voltage, frequency, and similar.